Qualitative and Quantitative Content Determination of Macro-Minor Elements in Bryonia Alba L. Roots using Flame Atomic Absorption Spectroscopy Technique - Uliana Vladimirovna Karpiuk; Khaldun Mohammad Al Azzam; Zead Helmi Mahmoud Abudayeh; Viktoria Kislichenko; Ahmad Naddaf; Irina Cholak; Oksana Yemelianova (Tabriz University of Medical Sciences, 2016)
Purpose: To determine the elements in Bryonia alba L. roots, collected from the Crimean Peninsula region in Ukraine. Methods: Dry ashing was used as a flexible method and all elements were determined using atomic absorption spectrometry (AAS) equipped with flame and graphite furnace. Results: The average concentrations of the determined elements, expressed as mg/100 g dry weight of the sample, were as follow: 13.000 for Fe, 78.000 for Si, 88.000 for P, 7.800 for Al, 0.130 for Mn, 105.000 for Mg, 0.030 for Pb, 0.052 for Ni, 0.030 for Mo, 210.000 for Ca, 0.130 for Cu, 5.200 for Zn, 13.000 for Na, 1170.000 for K, 0.780 for Sr, 0.030 for Co, 0.010 for Cd, 0.010 for As, and 0.010 for Hg. Toxic elements such as Cd and Pb were also found but at very low concentration. Among the analyzed elements, K was the most abundant followed by Ca, Mg, P, Si, Fe, Na, and Zn, whereas Hg, As, Cd, Co, Mo, and Pb were found in low concentration. Conclusion: The results suggest that the roots of Bryonia alba L. plant has potential medicinal property through their high element contents present. Moreover, it showed that the AAS method is a simple, fast, and reliable for the determination of elements in plant materials. The obtained results of the current study provide justification for the usage of such fruit in daily diet for nutrition and for medicinal usage in the treatment of various diseases.